Quantum squeezing via self-induced transparency in a photonic crystal fiber - Najafabadi, M. S.; Sánchez-Soto, L. L.; Corney, J. F.; Kalinin, N.; Sorokin, A. A.; Leuchs, G. (Physical Review Research, 2024)
We study the quantum squeezing produced in self-induced transparency in a photonic crystal fiber by performing a fully quantum simulation based on the positive P representation. The amplitude squeezing depends on the area of the initial pulse: When the area is 2π, there is no energy absorption and no amplitude squeezing. However, when the area is between 2π and 3π, one observes amplitude-dependent energy absorption and a significant amount of squeezing. We also investigate the effect of damping, detuning, and temperature: The results indicate that a heightened atom-pulse coupling, caused by an increase in the spontaneous emission ratio, reduces the amplitude squeezing.
CRIS-Team Scopus Importer:2024-05-24